Efficacy, safety and therapeutic mechanism of Shen-Qi Xiao-Tan formula in the treatment of peripheral atherosclerosis in patients with type 2 diabetes mellitus: a randomized, double-blind, placebo-controlled trial protocol - Yulin Leng; Xiaoxu Fu; Lisen Qian; Qiqi Li; Hong Gao; Hongyan Xie; Chunguang Xie (BMC, 2022)
Abstract Background Peripheral atherosclerosis is a common macrovascular complication of diabetes, but the treatment is limited. Chinese herbal medicine is the complementary and alternative therapy to delay the progression of atherosclerosis and reduce blood glucose and lipids. Shen-Qi Xiao-Tan (SQXT) formula is one of the prescriptions commonly used to treat diabetic peripheral atherosclerosis, but there is still a lack of high-quality evidence-based evidence. Methods This is a randomized, double-blind, placebo-controlled add-on trial that is expected to enroll 114 diabetic patients with peripheral atherosclerosis. After a 2-week run-in period, participants will been randomly assigned in a 1:1 ratio and receive 12 weeks of usual treatment and SQXT formula (treatment group) or usual treatment and placebo (control group). The primary outcome is the change in carotid intima-media thickness from baseline to endpoint. The secondary outcomes are the structure and function of peripheral arteries, blood glucose and lipids, traditional Chinese medicine syndrome score, and quality of life, and safety and endpoint events are evaluated. To explore the therapeutic mechanism through oxidative stress, inflammation, and advanced glycation end products, and lipidomics will be used to screen for biomarkers for diagnosis and efficacy evaluation. Discussion The objective of this trial is to evaluate the efficacy, safety and therapeutic mechanism of SQXT formula in the treatment of diabetic peripheral atherosclerosis. It will obtain high-quality evidence-based evidence and promote the treatment of diabetic macroangiopathy and the research and development of new drugs. Trial registration This trial is registered on Chinese Clinical Trials.gov with number ChiCTR2100047189 on 10 Jun 2021, and has been approved by the Ethical Review Committee of Hospital of Chengdu University of Traditional Chinese Medicine with number 2020KL-080.